Top-down generated micro- and nanoplastics reduce macrophage viability without eliciting a pro-inflammatory response - Annemijne E. T. van den Berg; Kas J. Adriaans; Luke A. Parker; Elena M. Höppener; Hanna M. Dusza; Juliette Legler; Raymond H.H. Pieters (Microplastics and Nanoplastics)
Abstract The presence of micro- and nanoplastic particles (MNPs) in our environment, food and drinking water has raised public concern due to inevitable human exposure. MNPs can be intentionally added to products or formed from plastics through fragmentation in the environment. Macrophages may become activated upon encountering MNPs, potentially triggering inflammation. However, this process, particularly in response to fragmented MNPs, remains poorly understood. This study aims to investigate whether fragmented MNPs have cytotoxic and pro-inflammatory effects on human macrophages. We examined the immunotoxic effects of mechanically degraded secondary polyvinylchloride, polypropylene and polyamide particles (PVC, PP; < 1 μm and 1–5 μm, PA6.6; 1–5 µm), in addition to primary polystyrene beads (PS; 0.05, 0.2 and 1 μm) and titanium dioxide particles (TiO2; < 0.1 μm) on human THP-1 macrophages. After up to 24 h of exposure to 1, 10 and 100 μg/ml, uptake was determined through flow cytometry and confocal microscopy, and effects on macrophages were measured by assessing lysosomal activity, mitochondrial activity, lactate dehydrogenase leakage, NF-κB activity and cytokine secretion. PS particles were taken up by macrophages in a concentration-, time-, and size-dependent manner based on particle mass. Additionally, MNPs increased lysosomal activity, suggesting potential accumulation of the particles. Fragmented MNPs induced a decrease in mitochondrial activity and an increase in LDH leakage depending on concentration, specifying their cytotoxic potential. However, at these levels, they did not significantly induce NF-κB activity and cytokine production (IL-6, IL-1β, TNF-α). Our findings suggest a lack of a direct pro-inflammatory response by macrophages to fragmented MNPs of various polymer types. However, higher exposure concentrations induced cytotoxicity, which may indirectly influence immune system functioning. This work emphasizes the importance of studying environmentally relevant MNPs to provide deeper insights into potential health impact of physico-chemically altered MNPs.